Investigation into the optimal acquisition and employment strategies with concentration on the VLCC East Suez market - Siti Aminah Sulaiman. (2013)
The aim of this research project is to ascertain the optimal employment and acquisition portfolio of 10 different Very Large Crude Carrier (VLCC) from the period 2000 to 2011. This experiment will be done on the assumption of perfect hindsight over the last 12 years.